Sintesis dan Karaterisasi CuO/rGO - Maulana, M Sifal; Riyani, Kapti; Setyaningtyas, Tien (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Semiconductor material is a material that is widely used in the chemical industry, especially as a photocatalyst. CuO is a semiconductor material that is active in the visible light range. Semiconductor materials can undergo recombination, rGO was used as a composite material into CuO to reduce recombination in this study. This study aims to look at the characteristics of the synthesized CuO/rGO. The processes performed include synthesis of CuO/rGO and characterization of CuO/rGO. The XRD results show the peaks of the diffractogram indicating of rGO peaks interpreted (002), peaks at (110), (-111), (111), (-202), (020), (202), (-113), (- 331), (220), (311) and (004) indicate the monoclinic phase of CuO has been formed. FTIR results indicating Cu-OH absorption show peak at wave numbers 3441.0 cm-1 and 894.97 cm-1, O-C-O vibrations present in CuO/rGO indicating adsorption at 2360.8 cm-1, 1975.1 and 1512 .1 cm-1 appears due to the C=C stretching vibrations in the rGO layer, 1033.8 cm-1 absorbs C-O stretching vibrations and 609.51 and 439.77 cm-1 have relative peaks indicating Cu-O stretching vibrations. The DRS results show that CuO/rGO has band gap value of 1.54 eV.